Fifty years of wildfowl ringing by The Wildfowl & Wetlands Trust - Mitchell, Carl; Ogilvie, Malcolm (Wildfowl, 1996)
When the British section of the International Council for Bird Preservation (ICBP) set up their Wildfowl Inquiry in the late 1930s, their over-riding objective was clear; to establish the reasons for perceived declines in wildfowl numbers. They stimulated the capture and ringing of ducks to answer one simple question; where do our wintering stocks come from? By 1937, responsibility for the ringing scheme had been transferred to the British Trust for Ornithology (BTO) and all subsequent rings bore the address of the British Museum (Natural History). The Wildfowl & Wetlands Trust (WWT) was making a substantial contribution to the ringing effort soon after its establishment in 1946 and, in 1954, responsibility for wildfowl ringing was transferred from the Wildfowl Inquiry Committee to WWT. Peter Scott had realised that, at the outset, it was vital to discover the origins and migration routes of all wildfowl species wintering in Britain and, at the same time, to build up a nationwide team of counters who could simultaneously record wildfowl numbers. Early examination of the ringing and recovery datasets by Hugh Boyd and others, generated mostly by WWT's ringing activities, became the foundation of what was known about flyways and survival of British wintering wildfowl.